Investigation of 137Cs and 90Sr transfer from sandy soil to Scots pine (Pinus sylvestris L.) rings - Ingrida Pliopaitė Bataitienė; Donatas Butkus (Journal of Environmental Engineering and Landscape Management, 2010)
Artificial radionuclides entered the environment mostly as a result of nuclear explosions, accidents at nuclear power plants and are entering due to the operation of the nuclear industry. After entering the environment, radionuclides spread globally at the world level, affect all environmental components and accumulate here. One of such environmental components is the tree. It, as if a historical chronicle, fixes the previous contamination and the former climatic conditions. One of the ways to read that chronicle is to estimate the radionuclide soil‐to‐tree transfer factors and coefficients.